Предмет: Математика,
автор: Кристина28121
решите пожалуйста ))))
Приложения:
Ответы
Автор ответа:
0
6/(х+2) - (х+2)/(х-2)+х²/(х-2)(х+2)=0
6(х-2) - х²+4 + х²=0
(х² сокращаются)
6х-12+4=0
6х-8=0
6х=8
х=8/6
х=1целая1/3
6(х-2) - х²+4 + х²=0
(х² сокращаются)
6х-12+4=0
6х-8=0
6х=8
х=8/6
х=1целая1/3
Похожие вопросы
Предмет: Алгебра,
автор: kamkar452
Предмет: Алгебра,
автор: BigClowd
Предмет: Английский язык,
автор: vasinaekaterina17062
Предмет: Математика,
автор: sergeyserrgey
Предмет: Физика,
автор: 1ilyxa1